Addiction: Disease and/or Social Construct - Zobenica, Adela J. (Sociološki pregled, 2019)
The paper deals with the concept of addiction and its deconstruction. There are different approaches to its study: as a disease, vice, sin, criminal behavior, social construct, weakness of character, genetically conditioned state, or the combination of the above. We present the development of social thought about addiction in the historical and cultural context and so we reach the “official view of addiction”, which is essentially a biomedical model. Through inconsistencies that come out of it, we “return” addiction to the social context, design a new meaning and consider the future of the concept. In conclusion, we suggest the possibility of overcoming the dichotomy arising from the title in terms of its practical application. Keywords: addiction, medicalization, inconsistencies of the biomedical model